Prevalence and Outcome of Cardio-Embolic Stroke Patients Admitted at Referral Neurology Hospital in Bangladesh - Sayeed, S K Jakaria Been; Haque, AKM Mahmudul; Moniruzzaman, Md.; Mahmud, Reaz; Das, Subir Chandra; Rashid, Mohammad Bazlur; Rahman, Sabrina; Mostafa, Golam; Nayeem, Abu; Chowdhury, Jahirul Hoque; et al. (Cardiology and Cardiovascular Medicine, 2022)
Background: Among ischemic stroke, cardio-embolic has both higher severity and mortality. Objective: To find out clinical outcomes and determine predictors of mortality related to cardio-embolic stroke. Methodology: This prospective cohort study was conducted among patients of acute ischemic stroke of cardiac origin. Patients were kept under follow-up to 90 days from discharge. A multivariate regression analysis was done to find out factors associated with mortality. Results: A total of 689 ischemic stroke patients were screened, 156 had confirmed Cardio-embolic stroke, and hospital frequency of cardioembolic stroke was 22.64%. NIH Stroke scale score (median, IQR) during admission was 13 [7- 19]. Overall mortality was 47 (29.9%). Modified Rankin score at 90 days was 2 [min 0, max 5] those who survived. Factors associated with mortality (odds ratio, [95% CI], p value) were acute myocardial infarction (1.6 [1.14 – 2.52] , 0.04), reduced ejection fraction (3.4 [2.17-5.27], <0.001), hypotension (3.1 [2.07 – 4.68], < 0.001), chronic kidney disease (1.8 [1.06 - 3.10], 0.04), raised Creatinine (2.4 [1.52 -3.84], 0.01), raised blood sugar (1.8 [1.14 - 2.89], 0.02), severe stroke (4.5 [3.57 – 7.03], <0.001), large infarct (5.7 [4.59 - 7.47], < 0.001), hemorrhagic transformation (4.43 [2.89 – 6.84], < 0.001) and aspiration pneumonia (1.9 [1.28-2.39], 0.01). Conclusions: Overall frequency, severity, functional disability, and mortality in cardio-embolic stroke are higher. Acute myocardial infarction, severe stroke, presence of hyperglycemia, hypotension, renal impairment, low ejection fraction, large infarct, hemorrhagic transformations, and aspiration pneumonia are both clinically and statistically significantly associated with mort